Engaging with Postmodernist Anthropology: Potential and Prospects for Digital Anthropology in Vietnam - Nguyen Truong Giang (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Digital anthropology is the anthropological discipline of the relationship between humans and digital technology. It has been emerging from the Fourth Industrial Revolution, which began at the beginning of the twenty-first century with new technologies. With interaction among people both in physical life and online, the change in method of digital anthropology is closely tied to the theoretical changes in anthropology, especially the formation of postmodern theory emerging from the early 1980s of the twentieth century and its practice to this day. Since post-modern anthropologists concentrate on voices, authority, and power relations between anthropologists and their informants, they call for a more “collective” and “participatory” approach to research and dialogue instead of monologues. To discuss potentials and prospects in Vietnam, this study shows the author’s understandings of the historical development of digital anthropology in the world and how this knowledge can be useful for cultural development in communities by engaging postmodernist anthropology with digital anthropology in Vietnam. In the past 20 years, in Vietnam, digital anthropology, also known as visual form, has taken steps to form and has good prospects; however, there is not yet a digital anthropology center with all its functions and duties. Adopting the postmodern turn in anthropology to empower local people in anthropological research, Vietnamese digital anthropologists have changed their roles in ethnographical fieldwork towards shared anthropology. Having experiences with visual anthropology over 20 years, the author foresees a young digital anthropology that requires strong support from traditional theories, especially post-modernist anthropology theories. Received 19th February 2020; Revised 17th September 2020; Accepted 28th September 2020